(untitled) (Research, Society and Development, 2023)
The present research aims to analyze community participation in the decision-making process for environmental sanitation and its impact on public health in the Municipality of Quelimane, with a focus on the 3 de Fevereiro Neighborhood. Sanitation is essential to ensure a healthy environment and improve the quality of life in society. To conduct this study, methods such as literature review, interviews, and questionnaires were used. The results were obtained through participant responses, data analysis, and organization in an Excel database. The selected sample consisted of 45 individuals, including men and women between the ages of 28 and 60, residing in 10 blocks of the neighborhood. Community participation can bring about various positive outcomes and impacts, such as improved waste management, promotion of sustainable sanitation practices, increased access to sanitation services, and awareness of the importance of hygiene and environmental sanitation. However, for better results, community involvement is crucial in all approaches and strategies at all levels. Community participation can bring significant benefits to waste management and the promotion of sustainable sanitation practices, thus enhancing the quality of life for the population.